Strategies for Maintaining Business during the Pandemic Era at a Store in Tanjung Pura - Febriana Sakina; Zuhrinal M. Nawawi (International Journal Labs, 2022)
The world is being hit by a covid-19 pandemic including Indonesia. To break the chain of spreading of the virus, The government asks every people to stay at home. This situation has an impact on economic instability and affected UMKM, no exception in MDI Collection Store. Therefore, a survival strategy for UMKM is needed to continue business during the pandemic, This study uses a qualitative data analysis method with a phenomenological approach. The data collection method is using the interview method, observation method, and documentation method. The result of this study recommends 4 ways a survival strategy for UMKM. There are using e-commerce for business, using digital marketing, improving product and service quality, and optimizing customer relationship marketing. The result of this study are important to be understood and adopted by UMKM and hopefully, they are always responsive and adjust to the business environment to survive.